2018
DOI: 10.3233/mnm-17186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nutraceutical multicompound including bergamot (Citrus Bergamia Risso) juice on metabolic syndrome: A pilot study

Abstract: BACKGROUND: The role of lipid-lowering and hypoglycemic nutraceuticals in cardiovascular disease prevention is the focus in recent years. The most studied compounds and plants are sterols, soy, red fermented rice, policosanols, artichoke, berberine. Epidemiological and experimental evidences suggest that dietary polyphenols, especially flavonoids, might play a role in preventing atherosclerosis, owing to their pleiotropic metabolic, anti-inflammatory and antioxidant effects. Recent studies have shown that berg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Finally, in a study conducted by Toth et al (2015), 80 patients with hypercholesterolemia received 150 mg/day of flavonoids coming from bergamot during 180 days. Authors described similar reductions in total cholesterol (13.2%), LDL cholesterol (18.2%) and triglycerides (16.5%) than those reported by Di Folco et al (2018) and Campolongo et al (2016).…”
Section: Change On Lipid Profilesupporting
confidence: 59%
See 1 more Smart Citation
“…Finally, in a study conducted by Toth et al (2015), 80 patients with hypercholesterolemia received 150 mg/day of flavonoids coming from bergamot during 180 days. Authors described similar reductions in total cholesterol (13.2%), LDL cholesterol (18.2%) and triglycerides (16.5%) than those reported by Di Folco et al (2018) and Campolongo et al (2016).…”
Section: Change On Lipid Profilesupporting
confidence: 59%
“…All of them found statistically significant decreases both in total cholesterol, LDL cholesterol and triglycerides. Di Folco et al (2018) recruited 80 subjects with overweight and metabolic syndrome, who were randomized to a low-calorie Mediterranean diet (control group) or the same intervention plus 200 mg/day of a dry extract of bergamot juice with 120 mg of phytosterols. Only the intervention group (supplemented with 200 mg/day of bergamot) showed significant reductions in total cholesterol (15.2%), LDL cholesterol (22.1%) and triglycerides (11.5%) concentration with respect to the baseline.…”
Section: Change On Lipid Profilementioning
confidence: 99%
“…The total mean age and total BMI of study participants ranged from 3.69–57 years and 25.95–65.2 kg/m 2 , respectively. The studies were conducted in Italy (Campolongo et al, 2016; Cicero et al, 2019; Di Folco et al, 2018; Ferro et al, 2020; Landi et al, 2019), India (Hancke et al, 2021), Greece (Florentin et al, 2019), China (Cai, Xing, et al, 2017), and United States (Dahlberg et al, 2017). The target populations were also patients with metabolic syndrome (Di Folco et al, 2018; Hancke et al, 2021), non‐alcoholic fatty liver disease (Ferro et al, 2020), prediabetes (Florentin et al, 2019), ischemic heart disease (Campolongo et al, 2016), and dyslipidemic overweight subjects (Cai, Xing, et al, 2017; Cicero et al, 2019; Dahlberg et al, 2017; Landi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the experimental studies, some evidence from human clinical trials explored the effects of bergamot (Capomolla et al, 2019; Gliozzi et al, 2013; Mollace et al, 2011, 2019; Rondanelli et al, 2021) and bergamot containing compounds supplementation (Cai et al, 2017; Campolongo et al, 2016; Cicero, Fogacci, Bove, Giovannini, & Borghi, 2019; Dahlberg et al, 2017; Di Folco et al, 2018; Ferro et al, 2020; Florentin, Liberopoulos, Elisaf, & Tsimihodimos, 2019; Hancke, Srivastava, Caceres, Burgos, & Alarcon, 2021; Landi et al, 2019) on lipid profiles and showed inconsistent results. Nevertheless, there is no meta‐analysis study to finalize the possible effectiveness of bergamot supplementation on lipid profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in animal models of type II diabetes, citrus flavanone‐O‐glycosides have shown a marked reduction in blood glucose levels (Akiyama et al, 2009). Citrus bergamia juice reduced blood glucose levels by 15% in patients diagnosed with metabolic syndrome (Di Folco et al, 2018). It has been shown that naringin, similarly to other polyphenols, significantly increases AMP kinase activity and glucose uptake in the muscle cells and liver (Janda et al, 2016; Mollace et al, 2011).…”
Section: Discussionmentioning
confidence: 99%